Feelings involved in the act of caring from the perspectivo of formal caregiver of the elderly (Research, Society and Development, 2025)
Introduction: The demographic profile of Brazil has undergone significant changes since the 1970s, marked by an increase in the age of the population. This demographic shift has led to transformations in illness patterns and epidemiology within society. Consequently, caregivers have assumed a pivotal role in caring for dependent patients. Despite the fact that formal caregivers are compensated for their services, there is a notable absence of guidelines to facilitate their professional development within Brazil. Objective: The primary goal of this study was to identify the socio-demographic characteristics of formal caregivers and gain insights into the emotions and sentiments they experience during their professional work. Method: This study was conducted using a qualitative, descriptive, and exploratory approach. Twenty formal caregivers from Itajubá, Minas Gerais (MG), participated in the study. The inclusion criteria stipulated that participants must be at least 18 years of age or older and have engaged in formal caregiving activities for at least six months. The exclusion criteria comprised recorded interviews that did not align with the research questions and incomplete sociodemographic characterization forms. Data analysis employed the Collective Subject Discourse method. Results: The study found that 70% of the participants were female, constituting the majority of the sample. Additionally, 70% of caregivers had between 5 and 9 years of education, and the average duration of their professional tenure exceeded six years, accounting for 65% of the total participants. The exploration of the theme "What emotions are experienced while being a formal caregiver?" yielded two central ideas: "Satisfaction and Enjoyment" and "Recognition." Conclusion: This study demonstrates that despite the challenges faced by caregivers in their professional duties, they derive satisfaction and recognition from the services they provide.